BIOACCUMULATION AND ELIMINATION RATE OF COBALT BY CAPOETA FUSCA UNDER CONTROLLED CONDITIONS - B. Mansouri; M. Ebrahimpour; A. Pourkhabbaz; H. Babaei; H. Farhangfar (Journal of Animal and Plant Sciences, 2012)
The objective of the present study was to investigate the pattern of accumulation and elimination of cobalt on selected organs of Capoeta fusca, after chronic exposure. During July to September 2010, C. fousca was obtained from qanat in Birjand. Cobalt accumulation and elimination were studied in fish exposed to one- thirty of LC50 taken as 6.8 mg/L of 96 hr LC50 concentration of cobalt over 30 days of exposure. The cobalt was assayed using Shimadzu AA 680 atomic absorption spectrophotometery and the results were given as μg/g wet wt (from fish). This finding showed that the accumulation patterns of cobalt are in the following order: liver>muscle>gill>skin. The elimination patterns of cobalt are in the following order: skin>gill>muscle>liver. The bioaccumulation and elimination of cobalt was significantly increased in the organs of C. fusca (p<0.01). The accumulation of cobalt in C. fusca was observed to be rapid and bioaccumulation increasing metal concentration in the water and with exposure time. In conclusion, the results of the present study showed that the accumulation and elimination of cobalt in C. fusca is dependent on organ and time.
Keywords: Capoeta fusca; exposure time; bioaccumulation and bio-elimination; cobalt toxicity